(untitled) (Journal of Pharmaceutical Negative Results, 2023)
With yearly incidence of 0.5% to 1.9%, kidney stones are one of the urinary tract conditions that are considered to impact at least 10% of the population in countries. 12% of Indians are estimated to have urinary stones and 50% of those cases result in the loss of one or both kidneys, as well as minor renal injury or loss. In the current investigation, a polyherbal formulation was made by choosing various herbs with strong antiurolithiatic properties. These plants have long been important in Indian culture. These plants are widely utilized throughout India and have been employed extensively in the ayurvedic medical system. The plant demonstrates a broad spectrum of pharmacological activities, including antibacterial, anti-helminthic, anti-pyretic, and many other effects.